Clustering of healthy lifestyle behaviors is associated with a lower incidence of adverse events in patients with newly diagnosed atrial fibrillation: a nationwide cohort study. (14th October 2021) - Lee, S R; Choi, E K; Han, K D; Oh, S; Lip, G Y H
Abstract: Background: Although unhealthy or healthy lifestyle behaviors tend to be clustered, studies on the risk of clinical outcomes depending on how the lifestyle behaviors are managed after atrial fibrillation (AF) diagnosis remain limited. Purpose: We aimed to evaluate the association between a cluster of healthy lifestyle behaviors and the risk of adverse outcomes in patients with AF. Methods: Using the Korean National Insurance Service database, patients who were newly diagnosed as nonvalvular AF between 2009 and 2016 and received national health screening examination within 2-year after AF diagnosis were included. A healthy lifestyle behavior score (HLS) was calculated by assigning 1 point each for "non-current" smoking, for non-drinking, and for performing regular exercise from the self-reported questionnaire in health screening examinations. The primary outcome was defined as major adverse cardiovascular events (MACE), including ischemic stroke, myocardial infarction, and hospitalization for heart failure. The secondary outcomes included individual components of the primary composite outcome and all-cause death. Results: A total of 208, 662 patients were included and 7.1%, 22.7%, 58.6%, and 11.6% were HLS 0, 1, 2, and 3 group, respectively. After multivariable adjustment, patients with HLS 1, 2, and 3 were associated with lower risks of MACE compared to those with HLS 0 (adjusted hazard ratio [95% confidence interval]: 0.788 [0.762–0.855], 0.654 [0.604–0.708], and 0.579 [0.527–0.636], respectively) (Figure). Increased number of healthy lifestyle behaviors were associated with lower risks of ischemic stroke, hospitalization for heart failure, and all-cause death. The risk reduction of healthy lifestyle combinations was consistently observed in various subgroups, regardless of CHA2DS2-VASc score and oral anticoagulant use. Conclusion: Increased number of healthy lifestyle behaviors were significantly associated with lower MACE and all-cause death risks in patients with new-onset AF. These findings support the promotion of a healthy lifestyle to reduce the risk of adverse events in AF patients. Funding Acknowledgement: Type of funding sources: None.